Waste Final Processing Site Based on Environment and Education in Banyumas, Central Java, Indonesia - Muslihudin Muslihudin; Wuryaningsih Tri; Wulan Tyas Retno; Kusumanegara Solahuddin; Ahdiati Triana; Purwono Purwono (E3S Web of Conferences, 2023)
One of the environmental problems found in developing countries, including Indonesia, is the waste problem. Waste management is the authority of the district or city government. Banyumas Regency is one of the areas that has experienced waste problems because the Final Processing Site (FPS) for its waste was closed and residents refused. In 2018, the Banyumas district received the title of waste emergency. At that time, in almost every corner of the city, there were piles of dirty and stinking garbage. Since the incident, it seems to be a whip for the local government to fix the waste problem. At present it can be said that they have been relatively successful in managing their waste, even to the point where the motto is that waste management is environmentally sound and educational. Based on that, it is interesting to study how the efforts were made and the criteria so that they dare to declare it as environmental and environmental-based waste management. The method used in this research is qualitative with interactive analysis. The results of the research show that waste management has been based on the environment with evidence in the form of; sorting waste from the source, processing which results in reducing the volume of waste at the sub-district and village level, product diversification from waste, processing into Refuse Derived Fuel (RDF) to achieve what is called zero waste. It has educational value because in the process of changing waste management through public education widely, especially in urban areas and more specifically to workers who are involved in various waste processing sites. In addition, the success of Banyumas Regency in managing waste is often used as a comparative study destination or a vehicle for education from various other local governments.